The Differences Between Motor Relearning Programme and Bobath Method On Standing Balance in Stroke Patients - Nisfil Mufidah (Journal of Global Pharma Technology, 2016)
Introduction: Stroke is a disorder of the central nervous system that can impair vital functions of the brain such as impaired coordination, impaired posture control, sensation, motion reflexes, and balance disorders such as the balance of sitting and standing. Complementary therapies like Motor Relearning Program (MRP) and Bobath Method have been involved. The aim was to analyze the differences between MRP and Bobath Method to increase standing balance in stroke patients. Method: A quasi-experimental research design is conducted, and respondents were divided into two groups. The treatment group was given the MRP and the control group was given the Bobath Method. Total sample 24 stroke patients were included as participants and obtained by simple random sampling. The independent variables were the MRP and Bobath Method. The dependent variable was standing balance. The data obtained by the Berg Balance Scale (BBS) analyzed using paired t-test and Independent t-test with a significance value of α≤0.05.  Results: The MRP (p=0.000) and Bobath method (p = 0.010) can improve standing balance. The differences in the effectiveness between MRP and Bobath Method showed a significance value of (p=0.006). Conclusion: Bobath method cause complex interactions of the sensory system and musculoskeletal and then regulated in the brain. Thus, MRP was more effective because it causes the cognitive, associative and autonomic to increase standing balance in stroke patients.Keywords: Bobath method; Stroke; Motor relearning program; Standing stability.